2022
DOI: 10.3390/v14020424
|View full text |Cite
|
Sign up to set email alerts
|

PRRSV Non-Structural Proteins Orchestrate Porcine E3 Ubiquitin Ligase RNF122 to Promote PRRSV Proliferation

Abstract: Ubiquitination plays a major role in immune regulation after viral infection. An alternatively spliced porcine E3 ubiquitin ligase RNF122 promoted PRRSV infection and upregulated in PRRSV-infected PAM cells was identified. We characterized the core promoter of RNF122, located between −550 to −470 bp upstream of the transcription start site (TSS), which displayed significant differential transcriptional activities in regulating the transcription and expression of RNF122. The transcription factor HLTF was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The main protein degradation pathways in eukaryotic cells are the ubiquitin-proteasome and autophagy-lysosome pathways. Our previous research has established that PRRSV can regulate the E3 ubiquitin ligase RNF122 to promote the K48 ubiquitination and degradation of MDA5 ( Sun et al., 2022 ). Autophagy can support or hinder viral replication depending on the viruses, cell types, or cellular environments ( Diao et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main protein degradation pathways in eukaryotic cells are the ubiquitin-proteasome and autophagy-lysosome pathways. Our previous research has established that PRRSV can regulate the E3 ubiquitin ligase RNF122 to promote the K48 ubiquitination and degradation of MDA5 ( Sun et al., 2022 ). Autophagy can support or hinder viral replication depending on the viruses, cell types, or cellular environments ( Diao et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV has evolved and employed various kinds of weapons to antagonize the host defense systems, and disruption of host transcription factors to evade innate immune responses is a common mechanism. Both the nonstructural proteins and structural proteins have been found to regulate different host transcription factors to favor PRRSV proliferation ( 31 , 32 , 44 46 ). In this study, we characterized the sequence from −89 to −14 bp upstream from the transcription start site (TSS) as the core promoter of Nat9 by using luciferase assay experiments and found that ETV5 acts as an activator and SP1 acts as a suppressor for the transcription of the Nat9 gene through binding to this region.…”
Section: Discussionmentioning
confidence: 99%
“…An E3 ubiquitin ligase ring finger 122 (RNF122) protein helicase-like transcription factor, which NSP1α and NSP7 downregulate, can inhibit RNF122 promoter activity and promote RNF122 transcription. RNF122 ubiquitinates the pathogen pattern recognition receptor melanoma differentiation-associated gene 5 (MDA5) protein via amino acid residues-K27 and K48, thereby degrading MDA5, inhibiting IFN production, and ultimately promoting virus proliferation [31]. Thus, this study provided new insights into the mechanism of action of NSP7 in viruses.…”
Section: Effect Of Nsp7 On Viral Replicationmentioning
confidence: 94%